Investigations of Slow Motions of the SLAC Linac Tunnel - Seryi, A (2000)
Investigations of slow transverse motion of the linac tunnel of the Stanford Linear Collider have been performed over period of about one month in December 1999 -- January 2000. The linac laser alignment system, equipped with a quadrant photodetector, allowed submicron resolution measurement of the motion of the middle of the linac tunnel with respect to its ends. Measurements revealed two major sources responsible for the observed relative motion. Variation of the external atmospheric pressure was found to be the most significant cause of short wavelength transverse motion of the tunnel. The long wavelength component of the motion has been also observed to have a large contribution from tidal effects. The measured data are essential for determination of parameters for the Next Linear Collider.